UJI EFEKTIVITAS ANTIDEPRESAN EKSTRAK BATANG SERAI (Cymbopogon nardus (L.) Rendle) TERHADAP MENCIT PUTIH JANTAN (Mus musculus) - Delisma Simorangkir (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2020)
Depression is a mood disorder that is characterized by profound and sustained sadness and sadness until the loss of life passion. Lemongrass which contains eugenol is thought to have the potential as an antidepressant that works by inhibiting the Mono Amine Oxidase enzyme. This study aims to determine the effectiveness of antidepressant citronella extract (Cymbopogon nardus (L.) Rendle) on male white mice. This study used 5 treatment groups namely CMC Na 0.5%, amitriptilyn, lemongrass extract dose 1.5 mg/kgBB, 15 mg/kgBB and 150 mg/kgBB. Antidepressant testing was determined based on immobility time using the forsed swim test method. Data analysis using statistics was tested for normality and continued with the One Way Anova method with a 95% confidence level. The results showed that the most effective treatment group as an antidepressant was amitriptilyn followed by lemongrass extract dose 150 mg/kgBB. The conclusion of this study is that lemongrass extract dose 150 mg/kgBB has the effectiveness as an antidepressant but is no more effective than the comparison of amitrip